22. COMPARISON OF SEALING ABILITY OF COLD LATERAL CONDENSATION AND SINGLE CONE OBTURATON TECHNIQUE: AN IN VITRO STUDY (Vietnam Journal of Community Medicine, 2022)
Objectives: To compare the sealing ability of two obturation techniques, cold lateral condensationand single cone.Methods: In vitro, thirty maxillary central incisors were divided into 2 groups. Group 1: Tooth werecleaned and shaped using K files with Crown-down technique. Root canals were obturated usingcold lateral condensation technique by AH26 sealer. Group 2: Cleaning and shaping by ProTaperhand used file system with Crown-down technique. Root canals were obturated with single conetechnique and AH26 sealer.Results: In group 2, voids increased gradually from 1/3 coronal to 1/3 apical of the root (medianof void percentage at 1/3 coronal: 1.68%, 1/3 middle: 0.41%, 1/3 apical: 0%). In group 1, voidsincreased gradually at 1/3 coronal to 1/3 apical (median of void percent at 1/3 coronal: 0.95%, 1/3middle: 0.79%, 1/3 apical: 0.2%). The area filled in group 2 is higher than the area filled in group 1at 1/3 middle and 1/3 apical (however, this difference was not statistically significant result (p>0.05).Conclusions: The difference is not statistically significant between the void percentages of 1/3coronal, 1/3 middle, and 1/3 apical between two study groups.
Keywords: Cold lateral condensation, single cone, Protaper, AH26.